ULTIMATUM - R. J. Pineiro, author 639526 (New York : A Tor Book, 1994)
Saddam Hussein is on the move again. This time armed with nuclear missiles pointed toward Tel Aviv and Tehran. The tension is pushed to the boiling point when Saddam's guns begin shooting down American planes in the Middle East. Aimed at provoking a new Gulf War, he leaves President Clinton no choice but to respond. From the author of The Intruders.